High nuclear poly-(ADP-ribose)-polymerase expression is prognostic of improved survival in pancreatic cancer - Klauschen, Frederick; Stenzinger, Albrecht; Weichert, Wilko (Histopathology, 2012)
High nuclear poly-(ADP-ribose)-polymerase expression is prognostic of improved survival in pancreatic cancer Aims: Poly-(ADP-ribose)-polymerases (PARPs) act as post-translational modifiers of proteins that are mainly involved in the DNA repair machinery, and have recently been shown to be predictive of pathologically complete remission after chemotherapy in breast cancer. In the pancreas, PARP expression has so far only been studied in inflammatory conditions. Therefore, in this study, we investigated the relevance of PARP in pancreatic cancer. Methods and results: Cytoplasmic and nuclear PARP expression was assessed by immunohistochemistry in a population-based cohort of 178 adenocarcinomas of the pancreas and correlated with clinicopathological parameters. We found that low-level nuclear expression of PARP is associated with a poor prognosis (median survival 9.6 versus 14.5 months, P = 0.004). Conclusions: Our analysis shows that nuclear PARP is an independent prognostic marker with respect to standard clinicopathological parameters. These results suggest that PARP should be further explored as a predictive factor with respect to conventional chemotherapy and concepts of PARP inhibitor therapy in pancreatic cancer.